DOKUMENTASI PENGGUNA SISTEM SKRINING “ANAK TANGGUH”, MEDIA SKRINING DIGITAL AUTISME BERBASIS M-CHAT-R/F DI INDONESIA - Rohmah, Arini Nur; Aji Ari Adam; Prilya Shanty Adrianie; Ariefin Nur Hidayat; Amri Zadi Hudaya; Galardhia Zain Azzahra; Naila Khairunnisa; Dedi Gunawan; Yusuf Sulistyo Nugroho (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
There is an increasing prevalence of Autism among Indonesian children. However, limited access, cost, and the lack of Indonesian-language screening tools present significant challenges for parents in the early detection of children with autism. A web-based digital system known as the